The Ethics of Institutional Analysis: Paternalism and Proprietary Access to Canadian U15 Faculty - Ellis, Taylor F.; Kouritzin, Sandra; Nakagawa, Satoru; Edgerton, Jason; Tamtik, Merli (Journal of Leadership, Accountability and Ethics, 2024)
Through an investigation of Canadian U15 faculty experiences with workload a common concern emerged regarding expansions to the bureaucratic and managerial functions of the university that negatively affect faculty members. These functions overlap with concerns about research ethics when Offices of Institutional Analysis (OIA) evaluate research projects, often justified as limiting faculty and student survey fatigue. Yet, secondary reviews by OIAs frequently manifest as additional ethical reviews, seeming to arise from a notion of paternalism whereby universities treat constituencies as property to be managed and controlled. Students, staff and faculty are constructed as being protected by this review process, framed as the University’s moral imperative. These bureaucratic add-ons negatively affect faculty, adding stress to initiating already complex research programs, thereby alienating research faculty. OIAs are normally established and governed by administrators and non-academic staff; they are, therefore, immune from direct faculty input and oversight. We raise concerns about institutional isomorphism, suggesting that discussion and possibly intervention are needed to prevent universal adoption of these processes throughout higher education.